Level of thought processes of the RCQ's in the Malaysian University English Test (MUET) reading component and students' performance: An analysis / Hiu Luang Peng, Ngo Kea Leng and Jeyamahla Veeravagu - Hiu, Luang Peng; Ngo, Kea Leng; Jeyamahla, Veeravagu (2006)
This study concerns the issues of large number out. Jengka undergraduates not obtaining strong bands in the MUET paper. which relates to their inability to answer correctly reading comprehension questions in the MUET paper. This research intends to provide educators same information on the level of thought processes of questions designed by the Malaysian Examination Council (Maljis Peperiksaan Malaysia) in the reading comprehension passages of the MUET paper and. therefore, equipping them with the necessary skills to perform tasks with regard to tackling reading comprehension questions. The findings indicate that the level of questions designed according to the level of thought processes advocated by the Bloom taxonomy has a bearing on the performance of the students in the MUET paper. It seems that the students face difficulties when answering higher order questions especially questions at the level of analysis, synthesis and evaluation. It also has an influence on the students' ability to answer higher order questions as compared to lower order questions. The findings conclude that there is a relationship between the level of thought processes on questions formation and the students' ability to answer them correctly. Such findings has provided a common base for further discussions and debate about our undergraduates competence in the English Language as well as the recommendations on the techniques that could be used to handle higher order level questions.